Unusual phenethylamine-containing alkaloids from Elaeocarpus tectorius. (February 2018) - Ezeoke, Margret Chinonso; Krishnan, Premanand; Sim, Dawn Su-Yin; Lim, Siew-Huah; Low, Yun-Yee; Chong, Kam-Weng; Lim, Kuan-Hon
Abstract: From the leaves of Elaeocarpus tectorius (Lour.) Poir. four previously undescribed phenethylamine-containing alkaloids were isolated, namely, tectoricine, possessing an unprecedented isoquinuclidinone ring system incorporating a phenethylamine moiety, tectoraline, representing a rare alkamide incorporating two phenethylamine moieties, and tectoramidines A and B, representing the first naturally occurring trimeric and dimeric phenethylamine alkaloids incorporating an amidine function. The structures of these alkaloids were established by detailed spectroscopic analysis. The absolute configuration of tectoricine was determined by comparison of the experimental and calculated ECD spectra. Plausible biosynthetic pathways to the four alkaloids are proposed. Graphical abstract: Four unusual phenethylamine-containing alkaloids were isolated from the leaves of Elaeocarpus tectorius (Lour.) Poir. Highlights: Tectoricine possesses an isoquinuclidinone ring system incorporating a phenethylamine moiety. Tectoraline represents a rare alkamide incorporating two phenethylamine moieties. Tectoramidines A and B are trimeric and dimeric phenethylamines possessing an amidine function. This represents the first isolation of phenethylamine-containing alkaloids from Elaeocarpus.